Pola Hubungan Sosial Di Daerah Transmigrasi Desa Kapidi, Kecamatan Mappedeceng, Kabupaten Luwu Utara (Studi Aspek Geografi Sosial) - Darsana, Putu (UNIVERSITAS NEGERI MAKASSAR, 2019)
The research aims to determine the social geography factors that support and hinder the associative relationship patterns, and patterns of social relationships that exist between community groups transmigration with local community groups. Population is 625 KK. Sampling using purposive sampling of 80 samples selected. Collecting data using observations, questionnaires and documentation. Qualitative data analysis.Results of the study are social geography factor determining patterns of social relationships. Seen from the public are not concerned about wide disparities ownership and land productivity with a percentage of 81.25 percent. Based on the distribution of settlements society rarely interact with the percentage of 67.50 percent. The use of local languages is 57.50 percent of the people do not matter. Factors religious differences, people do not visit each other when religious holidays with the percentage of 76.25 percent. Factors difference in the number of residents, community transmigration reluctant to interact with local communities. Differences in culture, inter-ethnic society visited each totaled 65 percent. Factor public infrastructure, has been fair with a percentage of 76.25 percent.The conclusion is the pattern of the relationship between local communities and society transmigration is associative relationship patterns. Social geography factor that supports associative relationship is a broad pattern of ownership of agricultural land, the level of productivity of the land, culture, public infrastructure and local languages. Social geography factors that inhibit the associative relationship is the distribution pattern of settlements, religious differences, and population.